2020
DOI: 10.3354/esr01068
|View full text |Cite
|
Sign up to set email alerts
|

Elevated accumulation of the toxic metal mercury in the Critically Endangered oceanic whitetip shark Carcharhinus longimanus from the northwestern Atlantic Ocean

Abstract: The oceanic whitetip shark Carcharhinus longimanus is a widely distributed large pelagic shark species once considered abundant in tropical and warm temperate waters, but recently listed as Critically Endangered by the IUCN due to drastic population declines associated with overfishing. In addition to risks posed to its populations due to overexploitation, oceanic whitetip sharks are also capable of accumulating elevated quantities of harmful environmental toxicants, placing them at special risk from anthropog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…There are other dimensions beyond biological sustainability that consumers are generally unaware of when choosing to consume or not consume a shark product. Most shark species are apex‐ or meso‐predators (Heupel et al, 2014) and frequent consumption of these species may disproportionately increase a consumer's exposure to many pollutants, including heavy metals, persistent organic pollutants and microplastics, which bioaccumulate and biomagnify through marine food webs (Gelsleichter et al, 2020; Tiktak et al, 2020). This can pose a serious risk to human health (Bosch et al, 2016a), particularly if consumers are unaware of what they are consuming due to product mislabelling (Biffi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…There are other dimensions beyond biological sustainability that consumers are generally unaware of when choosing to consume or not consume a shark product. Most shark species are apex‐ or meso‐predators (Heupel et al, 2014) and frequent consumption of these species may disproportionately increase a consumer's exposure to many pollutants, including heavy metals, persistent organic pollutants and microplastics, which bioaccumulate and biomagnify through marine food webs (Gelsleichter et al, 2020; Tiktak et al, 2020). This can pose a serious risk to human health (Bosch et al, 2016a), particularly if consumers are unaware of what they are consuming due to product mislabelling (Biffi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are comparable and within the range of other studies examining toxic metal concentrations in seafood throughout the world’s oceans and more specifically in sharks, ,,,, but it should be noted that each of these studies reported maximum values much higher than all of those we report here. Singapore has regulatory maximum limits for lead, cadmium, mercury, and arsenic in food products that are for sale.…”
Section: Resultsmentioning
confidence: 99%
“…Non-lethal skin and muscle samples can provide a variety of metrics that are useful in spatial ecology projects. Historically, tissues derived from muscle, scale, and skin biopsies have been used in the quantification of accumulated environmental toxicants ( Aerts et al, 2015 ; Alves et al, 2016 ; Gelsleichter et al, 2020 ; Charette et al, 2021 ; Stahl et al, 2021 ), isotopic compositions ( Cunjak et al, 2005 ; Kim et al, 2012 ; Busst et al, 2015 ; Peterson et al, 2017 ; TinHan et al, 2018 ), pathogenic microbes ( Bowers et al, 2008 ; Elliott et al, 2015 ), DNA ( John Nelson et al, 2003 ; Dominik et al, 2010 ; Smith et al, 2018 ; Thorstensen et al, 2019 ), and physiological metrics such as hormonal levels and tissue energy contents ( Fagan et al, 2012 ; Olsen et al, 2013 ; Verkamp et al, 2021 ). Koi ( Cyprinus carpio ) mucus was assayed for 11-ketotestosterone ( Schultz et al, 2005 ), while mucus was also useful for stable isotopes analysis of rainbow trout diet ( Salmo gairdneri ) ( Church et al, 2009 ), and DNA in Nile tilapia ( Oreochromis niloticus ) ( Taslima et al, 2016 ).…”
Section: Methods For Connecting Movement and Physiologymentioning
confidence: 99%